The Strategy For Developing Islamic Religious Education Materials That Are Contextual To The Lives Of Students At SMP Muhammadiyah 07 Medan - Jehanda Alhafiz Harahap (Yayasan Rahmat Islamiyah, 2024)
This study aims to examine the strategy for developing contextual Islamic Religious Education (IRE) material related to the lives of students at SMP Muhammadiyah 07 Medan. This research is a descriptive qualitative study. Data were collected through interviews, observations, and documentation. The data analysis technique used follows the Miles and Huberman model. The results indicate that IRE teachers have made efforts to connect the learning material with the students' life contexts, such as teenage interactions, digital ethics, and social relationships. Discussion and case simulation methods are applied to enhance student engagement. However, there are still challenges in developing more innovative materials due to reliance on rigid textbooks. Students respond positively to material that is relevant to their daily lives, although some feel that the material is sometimes too theoretical.